Antimicrobial prescribing patterns in a group of private primary health care clinics in South Africa - Norah L Katende-Kyenda; Martie S Lubbe; Jan HP Serfontein; Ilse Truter (AOSIS, 2007)
The aim of this study was to investigate the prescribing of antimicrobials in private primary health care in South Africa. ABSTRAK Die doel met hierdie studie was om die voorskryfpatrone van antimikrobiese middels in private primêre gesondheidsorginrigtings in Suid-Afrika te ondersoek.